1997
DOI: 10.1111/j.1469-7793.1997.001bf.x
|View full text |Cite
|
Sign up to set email alerts
|

Ca2+ and Na+ permeability of high‐threshold Ca2+ channels and their volt age‐dependent block by Mg2+ ions in chick sensory neurones

Abstract: 1. The Mg¥ block of Na¤ and Ca¥ currents through high-voltage activated (HVA; L_ and N_type) Ca¥ channels was studied in chick dorsal root ganglion neurones. 2. In low extracellular [Ca¥] (< 10¦Ì Ò) and with Naº and Cs¸as the main charge carriers (120 mÒ), HVA Na¤ currents started to activate at −40 mV, reached inward peak values near 0 mV and reversed at about +40 mV. 3. Addition of 30-500 ìÒ Mg¥ to the bath caused a strong depression of inward Na¤ currents that was voltage and dose dependent (KD = 39 ìÒ in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0

Year Published

1999
1999
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(41 citation statements)
references
References 39 publications
3
38
0
Order By: Relevance
“…It has been established that some calcium channels allow sodium influx in the absence of calcium that is blocked by magnesium (19,20). Thus, it was pertinent to explore whether the sodium-dependent depolarization induced by calcium removal was affected by magnesium.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been established that some calcium channels allow sodium influx in the absence of calcium that is blocked by magnesium (19,20). Thus, it was pertinent to explore whether the sodium-dependent depolarization induced by calcium removal was affected by magnesium.…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, the putative sodium channel may reveal the presence of a calcium channel in the plasma membrane that allows sodium permeation in the absence of external calcium. L-Type VDCC and transient receptor potential channels such as the SOCs allow large sodium currents when external calcium is brought to nanomolar and micromolar levels, respectively (19,20). In mature human sperm, there is a nifedipine-insensitive voltage-dependent calcium influx system, suggesting that these cells are endowed with VDCC (8,14).…”
Section: Figmentioning
confidence: 99%
“…It is also well known that the permeability of Ca¥ channels in the absence of external Ca¥ is altered and Ca¥ channels become permeable to monovalent cations (Matsuda, 1986). It has been reported that micromolar amounts of Ca¥ cause a strong depression of monovalent currents between −40 and 0 mV, which is effectively relieved at more positive potentials (Carbone et al 1997). It is thus possible that the outwardly rectifying currents recorded in Cs¤ and Na¤ solutions are attributable to cation permeability through Ca¥ channels.…”
Section: Effect Of Ca¥ Channel Blockersmentioning
confidence: 99%
“…In regards to the first possible mechanism, Yamaoka and Seyama [5] showed that, at physiologic levels and lower concentrations, [Mg 2+ ] i did not change single channel Ba 2+ current amplitude in cell-attached patches. Using excised membrane patches in the presence of BayK 8644, Kuo & Hess [6] also reported that cytosolic Mg 2+ , at concentrations greater or equal to 5 mM, could block inwardly-directed monovalent cation flux through single L-type channels, but Carbone et al [7] showed that Mg 2+ is much less able to block divalent than monovalent cation fluxes through the same channel type. These data would seem to argue against the possibility that physiologically-relevant [Mg 2+ ] i produce significant block of Ca 2+ permeation through the Ltype Ca 2+ channel.…”
Section: Introductionmentioning
confidence: 99%